2016
DOI: 10.1186/s12933-016-0345-1
|View full text |Cite
|
Sign up to set email alerts
|

Low circulating pentraxin 3 levels in pregnancy is associated with gestational diabetes and increased apoB/apoA ratio: a 5-year follow-up study

Abstract: BackgroundGestational diabetes mellitus (GDM) is a significant risk factor for cardiovascular disease (CVD) in later life. Pentraxin 3 (PTX3) is an essential component of innate immunity and independently associated with the risk of developing vascular events. The aim of the study was to examine the relationships between GDM, cardiovascular risk, and plasma PTX3 in pregnancy and at 5 years after the index pregnancy.MethodsThis population-based prospective cohort included 300 women who had an oral glucose toler… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 44 publications
1
22
1
Order By: Relevance
“…We and others have shown that women with a history of GDM display an unfavorable lipid profile [27, 33, 34] with enhanced ratios such as TG/HDL-C as a marker of cardiometabolic risk [27]. While leptin and adiponectin, and their association with measures of adiposity and glucose metabolism are well established in GDM, their associations with surrogate markers of CV risk in these women, or during normal pregnancy, are less documented.…”
Section: Discussionmentioning
confidence: 99%
“…We and others have shown that women with a history of GDM display an unfavorable lipid profile [27, 33, 34] with enhanced ratios such as TG/HDL-C as a marker of cardiometabolic risk [27]. While leptin and adiponectin, and their association with measures of adiposity and glucose metabolism are well established in GDM, their associations with surrogate markers of CV risk in these women, or during normal pregnancy, are less documented.…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of PAPP-A was investigated in pregnant women and found that it varies by ethnicity, gestational age, maternal weight and smoking status [3135]. The clinical investigations of the complex relationship among PAPP-A levels during pregnancy, gestational diabetes (GDM) and cardiovascular disease risk are evolving [3639]. Low levels of PAPP-A during the first trimester are associated with fetal Down’s syndrome [40] and other adverse events [37, 4143].…”
Section: Discussionmentioning
confidence: 99%
“…All samples were stored at −80°C and thawed less than three times. Adipokines (adipsin [DY1824], adiponectin [DY1065], chemerin [DY2324], leptin [DY398], resistin [DY1359], clusterin [DY5874]) and monocyte/macrophage markers (sCD163 [DY1607], sCD14 [DY383]) were measured in duplicate using commercially available antibodies (R&D Systems, Minneapolis, Minnesota) while CRP (DY1707) was measured as previously reported, also with commercially available antibodies (R&D Systems, Minneapolis, Minnesota), and IL‐1Ra (900 K574) was measured with antibodies from PeproTech (Rocky Hill, New Jersey), in a 384 format using the combination of a SELMA (Jena, Germany) pipetting robot and a BioTek (Winooski, Vermont) dispenser/washer (EL406). Absorption was read at 450 nm with wavelength correction set to 540 nm using an ELISA plate reader (Synergy H1 Hybrid, Biotek, Vinooski, Vermont).…”
Section: Methodsmentioning
confidence: 99%